Towards a sustainable nutrition paradigm in physique sport: A narrative review - Helms, E. R.; Prnjak, K.; Linardon, J. (Sports, 2019)
Physique athletes strive for low body fat with high lean mass and have higher body image and eating disorder rates than the general population, and even other weightlifting populations. Whether athletes with a background or tendency to develop these issues are drawn to the sport, or whether it drives these higher incidences, is unknown. However, the biological drive of cyclical energy restriction may contribute to binge-eating behavior. Additionally, requisite monitoring, manipulation, comparison, and judgement of one`s physique may contribute to body image concerns. Contest preparation necessitates manipulating body composition through energy restriction and increased expenditure, requiring dietary restraint and nutrition, exercise, and physique assessment. Thus, competitors are at mental health risk due to (1) pre-existing or predispositions to develop body image or eating disorders; (2) biological effects of energy restriction on eating psychology; and (3) dietary restraint attitudes and resultant physique, exercise, and nutrition monitoring behavior. In our narrative review we cover each factor, concluding with tentative best-practice recommendations, including dietary flexibility, slower weight loss, structured monitoring, gradual returns to offseason energy intakes, internal eating cues, appropriate offseason body compositions, and support from nutrition and mental health professionals. A mental health focus is a needed paradigm shift in bodybuilding nutrition practice and research